Refiguring the Body: Embodiment in South Asian Religions - Holdrege, Barbara A. (State University of New York Press, 2016)
Contents -- Introduction: Body Matters in South Asia -- The Essays -- Part 1: Material Bodies, Embodied Selves, and Perfected Embodiments -- Part 2: Divine Bodies and Devotional Bodies -- Part 3: Gendered and Engendering Bodies -- Contributions to Re-figuring Body Theories -- Beyond Human Embodiment -- Transforming Human Bodily Identities -- Notes -- References -- Part 1: Material Bodies, Embodied Selves, and Perfected Embodiments -- 1 Perfected Embodiment: A Buddhist-Inspired Challenge to Contemporary Theories of the Body -- The Materialist, Descriptivist Limitations of Contemporary Body Theories -- Beyond Modern Assumptions: Alternative Models from Religious Traditions -- Against an Exclusively Metaphorical Hermeneutic -- The Rejection of Sat-kāya-dṛṣṭi and the Realization of Dharma-kāya -- Challenges for Contemporary Body Theories -- Notes -- References -- 2 Body, Self, and Embodiment in the Sanskrit Classics of Āyurveda -- Self and Somatic Well-being -- The Material Body and the Embodied Self -- Self-cultivation -- The Cosmic Physiology -- Dharma and Body -- Notes -- References -- 3 Bodily Gestures and Embodied Awareness: Mudrā as the Bodily Seal of Being in the Trika Śaivism of Kashmir -- Mudrā as Mimetic Image -- Recollecting Abhinavagupta's Bodily Bearing -- Notes -- References -- 4 Bodied, Embodied, and Reflective Selves: Theorizing Performative Selfhood in South Indian Performance -- Scholarly Constructions of the Self -- A Theory of Performative Selfhood: Beyond Rasa Theory -- Effects of Possession on the Bodied, Embodied, and Reflective Selves -- Training the Performing Self in South Indian Classical Dance -- Conclusion: Constructing the Lingering Self -- Notes -- References -- Part 2: Divine Bodies and Devotional Bodies -- 5 Observations on the Bodies of the Gods in the Mahābhārata